Aminas bioativas e aminoácidos como índice de qualidade dos leites fermentados - Naiara Meireles Ciriaco (2018)
Bioactive amines and amino acids as quality criteria of fermented milk. The objective of this study was to investigate the potential use of amino acids and bioactive amines as an index of quality of fermented milk. The amino acid and amines were quantified by ultra efficient liquid chromatography. pH, total acidity and total solids were also analyzed. Within shelf life, fermented milk had pH of 4.03-4.06, total solids of 7.37 to 12.0 g/100 g and acidity of 0.82 to 1.00 g/100 g lactic acid. The samples had 3, 8 or 11 amino acids. All of them had asparagine and arginine; alanine, histidine, isoleucine, proline, tyrosine, threonine and valine were detected in three of them; phenylalanine was present in two and leucine, lysine and aspartic acid were present in one type of fermented milk. Total amino acids varied from 4.2 to 17.8 mg/kg.Spermine was the only amine detected in all fermented milk, at similar levels (0.67 to 0.80 mg/kg). As the shelf life expired, there was no significant difference on pH, total acidity and soluble solids. There was significant change on the types (1 to 3) and levels of some amino acids (except in two types of fermented milk). The levels of spermine increased and serotonin and agmatine were detected. The results were subjected to principal component analysis, and it was not possible to differentiate expired from good shelf life fermented milk.